2015
DOI: 10.6063/motricidade.6882
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de diferentes focos de atenção na performance motora de uma tarefa de agilidade em crianças

Abstract: RESUMOO objetivo do estudo foi investigar se instruções de foco externo de atenção comparado ao foco interno e sem foco determinado afetariam de forma diferente a performance motora de crianças. Adicionalmente, buscou-se mensurar a adoção das instruções prescritas sobre o foco de atenção pelos participantes. Vinte e três crianças, de ambos os sexos, com idade média de 10.04 ± .06 anos realizaram uma tarefa motora de agilidade em três condições diferentes: foco externo, foco interno e sem foco determinado. Este… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Several studies have reported that efficiency of motor learning and performance is highly dependent on attentional focus applied by the therapist. [ 3 , 4 , 11 , 13 , 14 ] Some studies have demonstrated that EF is superior to IF in terms of performance and learning of motor skills. [ 4 , 6 , 11 , 15 , 16 ] However, in the absence of adequate instructions regarding specific type of attentional focus, patients tend to use conscious mechanisms for task execution, generating difficulties and slowing information processing and task execution.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that efficiency of motor learning and performance is highly dependent on attentional focus applied by the therapist. [ 3 , 4 , 11 , 13 , 14 ] Some studies have demonstrated that EF is superior to IF in terms of performance and learning of motor skills. [ 4 , 6 , 11 , 15 , 16 ] However, in the absence of adequate instructions regarding specific type of attentional focus, patients tend to use conscious mechanisms for task execution, generating difficulties and slowing information processing and task execution.…”
Section: Introductionmentioning
confidence: 99%